2021
DOI: 10.1029/2020ja028442
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Space Weather Phenomena with Mars Plasma Environment During Solar Minimum 23/24

Abstract: We study the interaction of three solar wind (SW) structures, two stream interaction regions, and one interplanetary coronal mass ejection, with Mars’ plasma environment during November 20–27, 2007. This period corresponds to the solar minimum between the solar cycles 23 and 24 which was characterized by very low values of the SW density and dynamic pressure and low interplanetary magnetic field magnitude. During that time the Mars Express orbit was in the terminator plane, while the Earth, Sun, and Mars were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…While all energy fluxes are calculated during times when the spacecraft encounters the solar wind, per the Trotignon et al. (2006) empirical formula for the bow shock location, the bow shock is not a static boundary and can diverge from this formula, particularly during space weather events (Gruesbeck et al., 2018; Kajdić et al., 2021). When the bow shock is located further from Mars than the empirical formula suggests, we sample the sheath in addition to the solar wind.…”
Section: Datamentioning
confidence: 99%
“…While all energy fluxes are calculated during times when the spacecraft encounters the solar wind, per the Trotignon et al. (2006) empirical formula for the bow shock location, the bow shock is not a static boundary and can diverge from this formula, particularly during space weather events (Gruesbeck et al., 2018; Kajdić et al., 2021). When the bow shock is located further from Mars than the empirical formula suggests, we sample the sheath in addition to the solar wind.…”
Section: Datamentioning
confidence: 99%
“…During this Venus flyby, the orbit skimmed the bow shock. Kivelson et al (1991) used the magnetometer data to investigate the cross section of the bow shock. They found that it seemed to be smaller when its direction was aligned with the IMF when compared to when its direction was perpendicular to the IMF.…”
Section: Mariner 10 Galileo and Pioneer Venusmentioning
confidence: 99%
“…It is now well-accepted that ICMEs are the solar transients that have the greatest effect on the space environment and cause the most adverse space weather effect (Zhang et al 2021b). ICME events significantly affect the structure of the upper atmosphere and ionosphere of Mars, and influence the loss of ions to space (Jakosky et al 2015;Sánchez-Cano et al 2017;Kajdič et al 2021). Therefore, ICMEs play an important role in driving plasma escape and the evolution of the Martian atmosphere.…”
Section: Introductionmentioning
confidence: 99%